(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the theoretical and pedagogical analysis of modern tasks in the educational process, the results and effectiveness, the structure of the goal and the importance of political education in the upbringing of a harmoniously developed generation, its specific laws, principles and methods, as well as classification.